Effects Of Youtube Tutorial On Mental Computation Competency Of Pre-Service Teachers - Zulkifli, (Jurnal Serambi Ilmu, 2024)
This study aims at investigating the effect of youtube tutorials on mental computation competency among pre-service teachers. Mental computation might be viewed as a relatively new term among students and teachers. Therefore, introducing it to them need various methods and approaches. This study provided extra online material posted on youtube as a learning resource for pre-service teachers. The method used in this study was pre-experimental research with the type of one-group pretest-posttest design. The population of this study was Indonesian pre-service teachers and the sample was chosen by the technique of purposive sampling. The sample was from four universities in Indonesian, three public universities and one private university. The data were collected and analyzed both quantitatively and qualitatively. The quantitative approaches used in this study were the wilcoxon test and N-gain value. The result of the study showed that youtube tutorials have a significant impact on the improvement of pre-service teachers’ competency of mental computation.